Description of Mathematical Creative Thinking Ability of High School Students viewed from Metacognition Skills - Khasanah, Siti Uswatun; Widiyastuti, Erni (Jurnal Pendidikan MIPA, 2022)
Mathematical creative thinking ability is one of the skills that must be mastered in the 21st century. This study aims to describe the mathematical creative thinking ability of high school students in terms of metacognitive skills. The subjects used were students of class XI MIPA 5 SMA Negeri 3 Purwokerto. The sampling technique used is purposive sampling. The data were obtained from the results of the metacognition skill questionnaire, creative thinking ability test and interviews. Questionnaire data was used to classify students into categories of high, medium and low metacognitive skills. Test and interview data are used to describe mathematical creative thinking skills. The results showed that, students who have high metacognitive skills are able to master all indicators of creative thinking skills: 1) fluency; 2) flexibility; 3) originality; 4) elaboration. Then students with moderate metacognitive skills are able to master 3 indicators of creative thinking skills: 1) fluency; 2) originality; 3) elaboration. Meanwhile, students with low metacognition skills are only able to fulfil 2 indicators, namely originality and elaboration.Keywords: Mathematical creative thinking ability, metacognition skills, high school students.DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp1093-1108